The Relevance and Application of Risk Management in Small and Large Companies in Times of Unpredictable Change - Daniel BAUMANN (Communications of International Proceedings, 2023)
Due to the recent Ukraine war and the Corona crisis, coupled with pervasive political and economic instability, the future for many businesses has become highly uncertain and unpredictable. There's widespread speculation among these businesses about potential threats to their continuity. Reflecting on past experiences, many organizations question if they could have been better equipped to manage such extraordinary situations. Primarily, all businesses are subject to various types of risks, necessitating comprehensive risk management measures to mitigate potential adversities. The ISO 31000 risk management standard, along with other scholarly resources, provides a framework for addressing these risks. However, the central premise of this article revolves around the realization that the ISO 31000 standard, while generally known, does not specifically detail the implementation of particular management tools and techniques required to navigate through uncertain times effectively. The focus of this study is to acquire a detailed understanding of these management techniques and tools that can be leveraged to identify and manage risks across both large and small companies, and assess their impact on business development. It also aims to scrutinize how their implementation and impacts might differ in larger versus smaller organizations. The research methodology combines a thorough literature review with expert interviews spanning across multiple sectors, thereby providing an industry-independent perspective. This approach ensures a broader representation of results, offering a unique outlook on risk management practices in varying business sizes. The study synthesizes findings from ten expert interviews, offering a nuanced understanding of risk management strategies within the context of organizational scale and complexity.
Keywords: Risk; Risk management; ISO 31000